Introduction - Volzone, R.; Fontes, J. L. (Architectures of the soul: Diachronic and multidisciplinary readings, 2022)
The search for the wilderness as a space and possibility of a more radical religious experience accompanies and marks the development of Western culture, with multiple declinations, from voluntary seclusion or eremitical life to solitary life in more communitarian forms. The search for solitude and eremitism remained and marked the main moments of crisis and renewal in the Western world throughout the Middle Ages and the Early Modernity. All these experiences influenced and accompanied both the development of the city and the peri-urban landscape, with a particular importance in the transformation of territorially more isolated or peripheral areas. At the same time, the seek for solitude and seclusion, either through monastic or hermitic experiences, also flourished in other cultures and religious traditions, from Buddhism to Islam, giving interesting perspectives on the understanding of such religious phenomena in larger terms.